Biomarker for Asymptomatic Apical Periodontitis in Gingival Crevicular Fluid: aMMP-8 - Karteva, Teodora; Manchorova-Veleva, Neshka (European Journal of Dentistry, 2020)
Objectives Asymptomatic apical periodontitis (AAP) is one of the most widespread chronic inflammatory diseases in the field of dental medicine. Active matrix metalloproteinase (aMMP-8) previously demonstrated diagnostic potential as a biomarker for AAP in gingival crevicular fluid (GCF). The aim of this study was to determine the levels and diagnostic accuracy of aMMP-8 in GCF from teeth with AAP.Materials and Methods In this cross-sectional study, GCF samples were obtained from teeth with AAP (sample group, n = 31) and their contralateral teeth (control group, n = 31). Clinical and cone beam computed tomography (CBCT) parameters were used for the diagnosis and assessment of AAP and the determination of clinically healthy marginal periodontal tissues. One pool GCF sample per tooth was obtained from the whole crevice’s perimeter. aMMP-8 levels were determined by enzyme-linked immunosorbent assay (ELISA).Statistical Analysis Wilcoxon signed ranks test and Spearman rank correlation coefficient (rs) were used as statistical tools. The significance level was set at p < .05.Results The two groups demonstrated biomarker levels corresponding to a healthy marginal periodontal tissue. aMMP-8 levels were statistically and significantly higher in the samples collected from teeth with AAP. Lesions with greater volume showed correspondingly larger diameters. No statistically significant correlation between aMMP-8 levels and lesions’ volume or diameter was discovered.Conclusion GCF composition is modified by AAP only to a minimal extent. Further research is needed to substantiate the utilization of aMMP-8 as a potential biomarker for the diagnosis of the disease as well as to explore its relationship with other biomarkers.
Keywords: asymptomatic apical periodontitis; gingival crevicular fluid; aMMP-8; enzyme linked immunosorbent assay